Genome-wide analyses of miniature inverted-repeat transposable elements reveals new insights into the evolution of the Triticum-Aegilops group - Keidar-Friedman, Danielle (PLoS One, 2018)
The sequence drafts of wild emmer and bread wheat facilitated high resolution, genome-wide analysis of transposable elements (TEs), which account for up to 90% of the wheat genome. Despite extensive studies, the role of TEs in reshaping nascent polyploid genomes remains to be fully understood. In this study, we retrieved miniature inverted-repeat transposable elements (MITEs) from the recently published genome drafts of Triticum aestivum, Triticum turgidum ssp. dicoccoides, Aegilops tauschii and the available genome draft of Triticum urartu. Overall, 239,126 MITE insertions were retrieved, including 3,874 insertions of a newly identified, wheat-unique MITE family that we named “Inbar”. The Stowaway superfamily accounts for ~80% of the retrieved MITE insertions, while Thalos is the most abundant family. MITE insertions are distributed in the seven homologous chromosomes of the wild emmer and bread wheat genomes. The remarkably high level of insertions in the B sub-genome (~59% of total retrieved MITE insertions in the wild emmer genome draft, and ~41% in the bread wheat genome draft), emphasize its highly repetitive nature. Nearly 52% of all MITE insertions were found within or close (less than 100bp) to coding genes, and ~400 MITE sequences were found in the bread wheat transcriptome, indicating that MITEs might have a strong impact on wheat genome expression. In addition, ~40% of MITE insertions were found within TE sequences, and remarkably, ~90% of Inbar insertions were located in retrotransposon sequences. Our data thus shed new light on the role of MITEs in the diversification of allopolyploid wheat species.